Predictive Factors of Diabetes Mellitus Self-Management (DMSM) Practice: A Systematic Review and Meta-Analysis - Pamungkas, Rian Adi; Usman, Andi Mayasari; Chamroonsawasdi, Kanittha; Sari, Widia (Fakultas Ilmu-ilmu Kesehatan, 2024)
The diabetes mellitus self-management (DMSM) is integral to controlling blood glucose and preventing diabetes complications. There were still gaps in the analysis controversy of the outcome that need to be explored by systematic review and meta-analysis. The review aimed to synthesize the predictive factors associated with practice DMSM practice among Type 2 Diabetes Mellitus (T2DM). This study applied the systematic and meta-analysis method. Three databases, Scopus, PubMed, and Medline, were included in this study to obtain the relevant articles. Keywords used were “self-management”; “diabetes mellitus”; self-care; factors associated with self-management